Genetic diversity and complementary sex determination (CSD) in Dolerus aeneus (Hymenoptera, Symphyta): implications for the conservation of an ecologically-important sawfly - Cook, N.; Hubbard, S. F.; Karley, A. J.; Russell, J. R. (Conservation genetics, 2013)
Graminivorous sawfly numbers have declined steadily over recent years as a consequence of agricultural intensification. In spite of these declines and the importance of sawflies (Hymenoptera, Symphyta) as a food source for threatened populations of farmland birds, sawfly conservation studies have been restricted to census-based research. This is largely due to certain aspects of the sawfly life-cycle which make adequate sampling of these insects difficult. However, genetic research provides a valuable insight into population structure that cannot be obtained by traditional ecological means, and one which is essential for the development of conservation management strategies. In this study, we investigate the population genetic structure of the graminivorous sawfly Dolerus aeneus , and conduct a preliminary study to determine whether complementary sex determination (CSD), which can produce sterile diploid males under inbreeding conditions, operates in this species. Our research suggests that fragmentation of sawfly habitat as a result of agri-intensification has not yet acted to isolate D. aeneus populations, although some genetic effects are apparent (inbreeding and low diversity compared with other solitary Hymenoptera). In addition, diploid males were detected which may have compromised fertility and could indicate that CSD is operative in D. aeneus . This study highlights the need for further genetic research in sawflies to assess population structure on a UK-wide scale and to assess the prevalence of diploid males in key species. We discuss our findings in wider context of the genetics of Hymenoptera and the conservation and management of farmland biodiversity.